Resistance of Enterococcus spp. in Dust From Farm Animal Houses: A Retrospective Study - Liu, Mengda; Kemper, Nicole; Volkmann, Nina; Schulz, Jochen (Frontiers in Microbiology, 2018)
In a retrospective study, the antimicrobial susceptibility of Enterococcus spp. isolated from stored sedimentation dust samples from cattle, pig and poultry barns to 16 antibiotics was determined using a microdilution test. The resistance phenotypes of 70 isolates from different timespans (8 from the 1980s, 15 from the 1990s, 43 from the 2000s, and 4 from 2015) were determined. Resistant enterococci were detected in samples from all time periods. Resistances to three or more antibiotics occurred in 69 percent of all isolates. The oldest multidrug resistant isolate was an Enterococcus faecium obtained from a 35-year-old pig barn dust sample. No correlations ( = 0.16, p = 0.187) were found between the age of isolates and the number of resistances. Instead, the number of resistances were associated with the origin of the isolates. An exact logistic conditional regression analysis showed significant differences in resistance to ciprofloxacin, erythromycin, penicillin and tylosin between isolates from different animal groups. Interestingly, we isolated ciprofloxacin-resistant E. faecium from pig barn dust before fluoroquinolones were introduced into the market for use in animal husbandry. In conclusion, dust from farm animal houses is a reservoir and carrier of multidrug-resistant Enterococcus spp. People working in barns are unavoidably exposed to these bacteria. Furthermore, it can be hypothesized that emissions from barns of intensive livestock farming contaminate the environment with multidrug resistant enterococci.